Prenatal iodine intake and infant temperament in a multiethnic US cohort - Aderonke A Akinkugbe; Julia Duffy; Srimathi Kannan; Terryl J Hartman; Julio Landero; Michelle Bosquet Enlow; Robert O Wright; Xueying Zhang; Rosalind J Wright (Cambridge University Press, 2024)
Abstract Objective: Maternal iodine plays a central role in fetal neurodevelopment. It is recommended that pregnant women consume sufficient levels of iodine to accommodate increased need for mother and fetus. We examined associations among prenatal dietary and supplemental iodine intake and infant temperament. Design: The PRogramming of Intergenerational Stress Mechanisms (PRISM) study is an ongoing longitudinal pregnancy cohort. Data from 2011 to 2020 were used for this study. Women completed the Block98 FFQ ascertaining prenatal dietary and supplemental iodine intake and the Infant Behavior Questionnaire-Revised at infant age 6 months to ascertain infant temperament (Surgency/Extraversion, Negative Affectivity and Orienting/Regulation). Setting: USA. Participants: Mother-child dyads (n 892). Results: Women were primarily Black/Hispanic Black (44 %) and non-Black Hispanic (35 %) with 46 % reporting household income < $25 000/year. Nearly half had an estimated average requirement (EAR) < 160 µg/d (49 % based on dietary intake; 43 % based on diet and supplements). Girls born to women with an EAR ≥ 160 µg/d compared to girls born to women below this level had higher unadjusted extraversion scores for dietary plus supplemental intake (β = 0·23 (0·13, 0·33)); decreased to β = 0·05 (-0·08, 0·19) after adjusting for covariates. Boys born to women with an EAR ≥ 160 µg/d (based on diet and supplements) as compared to boys born to women below this level had statistically non-significant higher unadjusted negative affective score (β = 0·06 (-0·08, 0·20)) that became significantly lower upon covariate adjustment (β = -1·66 (-1·97, -1·35)). Conclusions: A significant proportion of these women reported suboptimal prenatal iodine intake. Suboptimal prenatal iodine intake may have implications for child neurodevelopment evident as early as infancy.